2000
DOI: 10.1666/0094-8373(2000)026<0019:tmgsrp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The muricid gastropod subfamily Rapaninae: phylogeny and ecological history

Abstract: Members of the neogastropod muricid subfamily Rapaninae are abundant, shallow-water predators whose phylogeny was previously investigated by Kool (1993b), who used mainly anatomical characters. In order to deepen understanding of the evolution of this important clade and to incorporate functional, ecological fossil evidence, we performed a phylogenetic analysis based on 34 shell characters in 45 genus-level taxa, including five muricid outgroups. Cladograms based on shell characters alone differed from those f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 59 publications
5
67
0
2
Order By: Relevance
“…The origin of the Ergalataxinae is difficult to determine, but appears to have been in the Eocene (Vermeij & Carlson, 2000;Claremont et al, 2013), with multiple varicate taxa from that time (Daphnellopsis, Odontopolys, Morula purulansis Martin, 1914, and Lyropupura). Ergalataxine varices are generally low and rounded, while they are flared in Lyndapterys and are mostly synchronized with two per whorl, even in the earliest L. vokesae Petuch, 1987 (E. Miocene) (Lozouet et al, 1994).…”
Section: Muricidaementioning
confidence: 99%
“…The origin of the Ergalataxinae is difficult to determine, but appears to have been in the Eocene (Vermeij & Carlson, 2000;Claremont et al, 2013), with multiple varicate taxa from that time (Daphnellopsis, Odontopolys, Morula purulansis Martin, 1914, and Lyropupura). Ergalataxine varices are generally low and rounded, while they are flared in Lyndapterys and are mostly synchronized with two per whorl, even in the earliest L. vokesae Petuch, 1987 (E. Miocene) (Lozouet et al, 1994).…”
Section: Muricidaementioning
confidence: 99%
“…This preference for hard‐parts in molluscan taxonomy and systematics has two causes: (1) material from which anatomical observations can be made is or has not been available to molluscan workers; or (2) detailed examination of molluscan anatomy has not led to the discovery of characters that are useful in taxonomic or phylogenetic analyses. This second point receives some support from phylogenetic analyses of muricid gastropods by Kool (1993) and Vermeij & Carlson (2000), who find that anatomical characters can resolve nodes deep in rapanine phylogeny but that they cannot be used to resolve the relationships of closely related species. In contrast shell characters can confidently be used to identify muricid species and can be useful in resolving the tips of trees.…”
Section: Introductionmentioning
confidence: 97%
“…Large, productive systems in which competition and predation are intense are therefore expected to serve as fountains of extralimital traits (Vermeij 2003). Vermeij and Carlson (2000), for example, showed that novel shell traits and new modes of life in the muricid gastropod clades Rapaninae and Ergalataxinae evolved most frequently during the Neogene epoch in the species-rich Indo-West Pacific region, stretching from the Red Sea and East Africa to eastern Polynesia. Subsequent work on other innovations has revealed many additional examples of adaptive phenotypic departures from the ancestral norm in ecosystems where selection due to enemies is intense.…”
mentioning
confidence: 99%